The Dual Impact of Exchange Rate Depreciation and Uncertainty on Budget Deficits of Pakistan - Malik Muhammad; Ume Kalsoom; Fozia Sultana (Al-Qanṭara, 2024)
This study examines the impact of exchange rate, exchange rate uncertainty and other macroeconomic variables on the budget deficit of Pakistan. By using data for the period 1982 to 2021, the ARDL Bounds Test confirmed a co-integration relationship among the variables. For regression analysis Fully Modified Least Squares (FMOLS) is used. Results reveal that currency depreciation positively affects the budget deficit due to increase in the cost of foreign debt services and imports, while exchange rate volatility worsens budget deficits by reducing trade and economic growth. Findings also show that instabilities of expenditure and revenue also increase the deficit due to dependence on unstable tax revenues and weak financial planning. Per capita GDP growth, used as a proxy for economic development, reduces deficits by increasing tax bases and raising government revenue. Findings further reveal that large government participation and seigniorage increase the budget deficits through inefficiencies and increase in inflation. Trade openness is found to decrease budget deficits as with the increase in openness i tax revenues from international trade also increases. Political regimes also significantly affect fiscal outcomes, with deficits being more evident under democratic governments. Debt servicing and interest rates are found to aggravate budget deficits, showing the cyclical nature of fiscal challenges of Pakistan. This study concludes that addressing exchange rate fluctuations, improving fiscal discipline, increasing economic growth, and enhancing trade openness are essential to achieving long-term fiscal sustainability in Pakistan.